Recurrent pulmonary embolism: is filarial lymphedema a risk factor for deep vein thrombosis? - Boo, Yang Liang; Lim, Hong Tak; Chin, Pek Woon; Lim, Suat Yee; Hoo, Fan Kee (Pakistan Medical Association, 2016)
Lymphatic filariasis is caused by nematodes that inhabit the lymphatic system and subcutaneous tissues. 90% of the infections are caused by Wuchereria bancrofti while most of the remainder by Brugia malayi and Brugia timori. The presence of filarial lymphedema or elephantiasis leads to disfigurement and disability. However, its relationship with deep vein thrombosis and pulmonary embolism was not well-documented. Here, we described a case of recurrent pulmonary embolism associated with left leg elephantiasis.